Low-melting metal bonded MM′X/In composite with largely enhanced mechanical property and anisotropic negative thermal expansion. (1st May 2022) - Zhou, He; Tao, Kun; Chen, Bo; Chen, Haodong; Qiao, Kaiming; Yu, Ziyuan; Cong, Junzhuang; Huang, Rongjin; Taskaev, Sergey V.; Zhang, Hu
Abstract: MM′X (M, M′ = transition metals, X = carbon or boron group elements) compounds experiencing magnetostructural transition have great potential in multifunctional applications due to the various magnetoresponsive effects. However, the poor mechanical properties hinder their practical applications. In the present work, the low-melting metal bonded MM′X/In composites are fabricated. The dense structure with low porosity, formed due to the high ductility of In, greatly improves the machinability and thermal conductivity. The thermal cycling tests prove the excellent integrality and stability of MM′X/In composites. The introduction of ductile In reduces the constraints of structural transition so that weakens the first-order magnetostructural transition of MM′X compounds, thus lowering the hysteresis loss. Besides, the MM′X/In composite with 30 wt.% In (In30) exhibits a larger magnetocaloric effect than that of the benchmark magnetocaloric material Gd. In addition, zero thermal expansion (ZTE) property is achieved in In30 composite over a wide temperature range. Moreover, magnetic oriented In30 composite displays a strongly anisotropic thermal expansion performance. An obvious positive thermal expansion (PTE) with linear PTE coefficient of 5.2 × 10 −6 K −1 is observed along the direction parallel to pressure, while large negative thermal expansion (NTE) can be obtained along the directions perpendicular and parallel to field. The NTE in the direction parallel to field is as high as −40.6 × 10 −6 K −1, which is comparable to those of some typical NTE materials. Consequently, the present result highlights the potential multifunctional applications of low-melting metal bonded MM′X/In composites, especially as magnetic refrigerants and NTE materials around room temperature. Graphical abstract: Image, graphical abstract